A STUDY ON THE COMPOUND WORD IN NATIONAL COLUMN IN THE JAKARTA POST NEWSPAPER PUBLISHED DECEMBER 2010 - APRILIA, KUSUMA (2011)
This research paper is aimed at answering two problems, namely what are the forms of compound word found in National column of The Jakarta Post newspaper, and what are the meanings of the compound found in National Column of The Jakarta Post Newspaper. The data are taken from National column of The Jakarta Post Newspaper published December 2010. To find the answer of the forms, she uses the theory of O'Grady. The type of this research paper is descriptive qualitative research. In collecting the data, the writer applied documentation method. The several steps are done to analyze the data such as reading and collecting the data. In analyzing the form of compound word, the step is analyzing with the employing the tree diagram. The research paper results are 240 data from national column of The Jakarta Post newspaper. The results are: the forms of compound word, and the meaning of compound word. The forms of compound word consist of noun compound (187 = 78%), adjective compound (17 = 7%), and verb compound (36 = 15%). Total is 240 (100%). The meaning of compound word consists of transparent meaning (83 = 35%), and opaque meaning (157 = 65%). Total is 240 (100%).